Impact of renewable energies on the indian power system: Energy meteorological influences and case study of eefects on existing power fleet for rajasthan state. (November 2018) - Horst, Daniel; Jentsch, Mareike; Pfennig, Maximilian; Mitra, Indradip; Bofinger, Stefan
Abstract: India is aiming at a large scale integration of renewable energy with an ambitious target of 100 GW solar and 60 GW wind, by 2022. For economical and optimal integration of such a high renewable energy (RE) capacity, detailed planning based on meteorological data is necessary. This study uses time series of wind and solar resource data in order to quantify the correlation, smoothing effect, simultaneity and seasonality at various spatial scales over the whole country. Additionally, a simplified power plant dispatch optimization for the state of Rajasthan has been done, for specific future scenarios. This attempt at assessing the grid impacts of variable Renewable Energy (vRE) for India could be a foundation block for vRE Integration efforts. Highlights: Large amount of vRE can be integrated into the electricity grid by 2022. Detailed scenario forecasts are developed. Key is correlation information of different units and flexibility requirements. Indian resource potential and smoothing effects are favourable. Increasing share of Renewables, spatial concentration of vRE has to be avoided.